2017
DOI: 10.1002/macp.201700544
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Initial Miscibility for Ternary Polyurethane Reaction Mixtures on Basis of Solubility Parameters and Flory–Huggins Theory

Abstract: The initial miscibility in bi‐soft segment polyurethane reaction mixtures is investigated on the basis of Flory–Huggins (FH) theory and solubility parameters (SPs). Different group contribution theories are applied to estimate the SPs of polyether polyol (PEP) structures and 1,6‐hexamethylene diisocyanate (HDI). The PEP structure comprising starter molecule, ethylene oxide/propylene oxide moieties, and end‐functional hydroxyl groups is considered in the calculations. Binodal curves are determined computational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
3
11
0
1
Order By: Relevance
“…Yet, detailed knowledge about miscibility and consequentially about the phase diagram of reaction mixtures is required and of particular importance for possible applications of RIPS . Applying Flory–Huggins theory in combination with solubility parameters allows one to calculate phase diagrams for partially miscible ternary bi‐soft segment reaction mixtures and thus to estimate their initial miscibility …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, detailed knowledge about miscibility and consequentially about the phase diagram of reaction mixtures is required and of particular importance for possible applications of RIPS . Applying Flory–Huggins theory in combination with solubility parameters allows one to calculate phase diagrams for partially miscible ternary bi‐soft segment reaction mixtures and thus to estimate their initial miscibility …”
Section: Introductionmentioning
confidence: 99%
“…In the study reported here, isocyanate‐terminated polyurethane (ITPU) oligomers consisting of 1,6‐hexamethylene diisocyanate (HDI), poly(propylene oxide) (PPG) and poly(ethylene oxide) (PEO) were prepared with varied soft segment composition. The chosen PPG components covered a molecular weight range of 400 to 4000 g mol −1 since it has been shown that within this range the molecular weight of PPG affects the miscibility with a PEO oligodiol soft segment ( M n = 590 g mol −1 , PEO600) . The RIPS occurring during the ITPU formation was investigated in detail and the initial miscibility of the reactants was correlated with the phase behaviour during the reaction towards bi‐soft segment ITPUs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a deep understanding of the underlying thermodynamics of RIPS is essential to tailor bi‐soft segment PUs. First approaches provide phase diagrams and initially miscibility of partially miscible ternary bi‐soft segment reaction mixtures 15,16…”
Section: Introductionmentioning
confidence: 99%
“…First approaches provide phase diagrams and initially miscibility of partially miscible ternary bi-soft segment reaction mixtures. [15,16] The present work intensifies the investigation and focuses on the phase evolution during the observed RIPS in order to provide a detailed description of the processes involved. Isocyanate (NCO) content titration, 1 H nuclear magnetic resonance ( 1 H-NMR) spectroscopy, size exclusion chromatography (SEC), and microscopy are applied to reveal the reaction kinetics and the phase compositions as a function of reaction mixture composition.…”
mentioning
confidence: 99%
“…Diese Trenntechnik kommt bei der Rückgewinnung von Essigsäure im Bereich der Spezialchemie vermehrt zum Einsatz . Aufgrund der instationären Betriebsweise und der Flüssig/Flüssig‐Entmischung ist die Auslegung und robuste Steuerung von solchen Prozessen relativ komplex .…”
Section: Introductionunclassified